Право працівника на відпочинок в Україні - Бєлицький, Д. М. (ХНУРЕ, 2020)
This article provides the reader with information about major violations of workers' rights to rest and how to protect them. This information is very relevant for today, as in our country, employers often cancel or indicate time for rest and breaks. Also, here you will learn how to properly use your rights so that you are not forced to work more without bonuses.
Keywords: філософія; право працівника на відпочинок